Survival and growth of Cronobacter sakazakii on fresh-cut fruit and the effect of UV-C illumination and electrolyzed water in the reduction of its population - Santo, David (2017)
Cronobacter sakazakii, found in foods such as powdered infant formula and plant origin ready-to-eat food, is an opportunistic pathogen to infants, neonates and vulnerable adults. The objective of this study was to monitor the growth of C. sakazakii in fresh-cut 'Royal gala' apple, 'Rocha' pear, and 'Piel de sapo' melon, and the effect of UV-C illumination, acidic electrolyzed water (AEW) and neutral electfolyzed water (NEW) in the reduction of its population. Fresh-cut fruits were inoculated and incubated at different temperatures during 10 days while monitoring C. sakazakii. The inhibitory activity of different doses of UV-C (0-10 kj.m(2)), electrolyzed water and sodium hypochlorite (SH) (100 ppm chlorine) was evaluated on the fruits inoculated with C sakazakii. The bacterium showed a significant growth in the fruits at 12 and 20 C, but did not grow at 4 C, despite having survived for TO days. At 8 C, adaptation phases of 0.6-3.9 days were estimated in the fruits before exponential growth. The UV-C 7.5 and 10 kJ/m(2) produced greater C. sakazakii population decreases (2-2.4 log cfu/g) than AEW (1.3-1.8 log cfu/g), NEW (1-12 log cfu/g) and SH (0.8-1.4 log cfu/g). The UV-C decontamination system and refrigeration at 4 degrees C, may contribute to the product's safety and quality. The results help better understand the behavior of C sakazakii on fresh-cut fruit alerting producers of the necessity to respect the high hygienic practices, adequate refrigerating temperature maintenance and caution with the tendency to prolong the validity of this kind of ready-to-eat food. (C) 2016 Elsevier B.V. All rights reserved.